A decade of Schismatoglottis species - Boyce, Peter C.; Wong, Sin Yeng (The International Aroid Society, Inc., 2008)
Despite the considerable popularity of Alocasia and Colocasia, the list of horticulturally important aroid species is overwhelmingly comprised of aroids from the American tropics: Anthurium, Philodendron, Dieffenbachia, Spathiphyllum, Monstera and Caladium being pre-eminent. Paradoxically, aside from Alocasia, species from the oldworld tropics that command horticultural attention, and even there an attention not or hardly addressed by the wholesale commercial trade, tend to be those grown primarily for the inflorescence: notably Amorphophallus, Arisaema and Typhonium although this in no way implies that the foliage of these magnificent Asians is not noteworthy.